Grocery shopping in the post pandemic era : A study in the Czech Republic - Vélez Taborda, Alejandra (2023)
The current thesis aims to identify and understand the reasons behind the changes in grocery shopping behavior among millennial consumers in the Czech Republic thanks to Covid-19 restrictions. In the qualitative study, Semi-structured In-depth Interview were applied to 13 Czech millennials, their responses were coded in MAXQDA and analyzed using the thematic approach. Among the 21 findings, the researcher identifies and explains the main changes in eating and grocery purchasing habits, preferences in grocery suppliers, changes in shopping frequency as well as online and offline perspectives. Some behaviors that are likely to continue in the future include the multichannel purchasing, usage of online and offline supermarkets for different segments of consumers, healthier approach to grocery shopping and the seek for foods, and even kitchen appliances, that make cooking more practical.